GABA through the Ages: Regulation of Cortical Function and Plasticity by Inhibitory Interneurons. (26th June 2012) - Lehmann, Konrad; Steinecke, André; Bolz, Jürgen
Abstract : Inhibitory interneurons comprise only about 20% of cortical neurons and thus constitute a clear minority compared to the vast number of excitatory projection neurons. They are, however, an influential minority with important roles in cortical maturation, function, and plasticity. In this paper, we will highlight the functional importance of cortical inhibition throughout brain development, starting with the embryonal formation of the cortex, proceeding by the regulation of sensory cortical plasticity in adulthood, and finishing with the GABA involvement in sensory information processing in old age.